The Complex Interaction Between the Major Sleep Symptoms, the Severity of Obstructive Sleep Apnea, and Sleep Quality - Frangopoulos, Frangiskos; Zannetos, Savvas; Nicolaou, Ivi; Economou, Nicholas-Tiberio; Adamide, Tonia; Georgiou, Andreas; Nikolaidis, Pantelis T.; Rosemann, Thomas; Knechtle, Beat; Trakada, Georgia (Frontiers in Psychiatry, 2021)
Introduction: Little information exists in the general population whether clinical presentation phenotypes of Obstructive Sleep Apnea (OSA) differ in terms of sleep quality and comorbidities. Aim: The purpose of our study was to assess possible differences between symptomatic and asymptomatic OSA patients concerning syndrome’s severity, patients’ sleep quality and comorbidities. Subjects and methods: First, in a nationwide, stratified, epidemiological survey, 4118 Cypriot adult participants were interviewed about sleep habits and complains. In the second stage of the survey, 264 randomly selected adults, underwent a type III sleep study for possible OSA. Additionally, they completed the Greek version of Pittsburgh Sleep Quality Index (Gr-PSQI), Epworth Sleeping Scale (ESS), Athens Insomnia Index (AIS) and Hospital Anxiety and Depression Scale (HADS). Results: From 264 enrolled participants, 155 individuals (40 females and 115 males) were first diagnosed with OSA. Among these 155 patients, 34% had ESS≥10 and 49% AIS≥6. One or both symptoms present, categorized the individual as symptomatic (60%) and neither major symptom as asymptomatic (40%).There were no statistical differences (SSD) between the two groups (symptomatic-asymptomatic) with regards to anthropometrics (age or gender, neck, abdomen and hip circumferences, Body Mass Index [BMI]). The two groups had no differences in OSA severity - as expressed by Apnea Hypopnea Index (AHI), Oxygen Desaturation Index (ODI), and mean oxyhemoglobin saturation (SaO2) - and in cardiometabolic comorbidities. Symptomatic patients expressed anxiety and depression more often than asymptomatics (p<0.001) and had poorer subjective sleep quality (Gr-PSQI, p<0.001). According to PSQI questionnaire, there were no SSD regarding hours in bed and the use of sleep medications but there were significant differences in the subjective perception of sleep quality (p<0.001), sleep efficiency (p<0.001), duration of sleep (p=0.001), sleep latency (p=0.007), daytime dysfunction (p<0.001), and finally sleep disturbances (p<0.001). Conclusion: According to our data, OSA patients reporting insomnia-like symptoms and / or sleepiness do not represent a more severe phenotype, by the classic definition of OSA, but their subjective sleep quality is compromised, causing a vicious circle of anxiety or depression.